2002
DOI: 10.1002/mar.10018
|View full text |Cite
|
Sign up to set email alerts
|

Sex, spies and celluloid: Movie content preference, choice, and involvement

Abstract: This study empirically tests the congruity between movie-content preference and choice on television, video, and at the cinema; and the impact of consumer involvement on this relationship. The results support the need to treat preference and choice differentially. Media type added little in way of explanation of changes in preferencechoice congruence. Involvement with movie choice was found to vary by medium, yet correlational analysis showed that it did not unequivocally change the nature of preference -choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, existing research has already shown that movie consumption is more spontaneous on television compared to video in Australia (Garlin and McGuiggan 2002) and on the cheaper video (VHS and DVD) rental channel, where customers also pay less attention to critics' reviews and Oscars, in the USA (Hennig-Thureau et al 2006). In line with this extant line of study, more systematic comparative analyses of consumer responses to track record and financial resources across distribution channels may lead industry professionals and cultural managers to new insights into film consumption and film finance.…”
Section: Discussionmentioning
confidence: 97%
“…However, existing research has already shown that movie consumption is more spontaneous on television compared to video in Australia (Garlin and McGuiggan 2002) and on the cheaper video (VHS and DVD) rental channel, where customers also pay less attention to critics' reviews and Oscars, in the USA (Hennig-Thureau et al 2006). In line with this extant line of study, more systematic comparative analyses of consumer responses to track record and financial resources across distribution channels may lead industry professionals and cultural managers to new insights into film consumption and film finance.…”
Section: Discussionmentioning
confidence: 97%
“…Correspondingly, marketing and economic scholars have started paying increasing attention to the many facets of these industries-Broadway shows and theaters (Caves, 2000;Holak, Havlena, & Kennedy, 1986;Reddy, Swaminathan, & Motley, 1998;Vogel, 2001), recorded music (Caves, 2000;Moe & Fader, 2001;Vogel, 2001), book publishing (Caves, 2000;Greco, 1997;Vogel, 2001), and movies (Elberse & Eliashberg, 2003;Eliashberg & Shugan, 1997;Garlin & McGuiggan, 2002;Krider & Weinberg, 1998;Lehmann & Weinberg, 2000;Vogel, 2001). Each year, approximately half a trillion dollars is spent globally on various forms of entertainment, and more than $200 billion of that total is spent in the United States (Vogel, 2001).…”
mentioning
confidence: 99%
“…They found that 'doing what friends were doing', 'doing something to match the mood the respondent was in', and 'doing something for a change' were the main tactics used. Garlin and McGuiggan (2002) found that choosing a film to watch at the cinema, as opposed to watching a film on video or television entailed a higher level of involvement. Involvement in this context refers to the importance of the purchase to the consumer and the risks entailed in the decision.…”
Section: The Repeat Viewing Phenomenonmentioning
confidence: 96%